The spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae)—Part 1: species groups, diagnoses, identification keys, distribution maps and revision of the argelasius-, coenobitus- and auricomis-groups - Jäger, Peter (Zootaxa, 2020)
The genus Olios Walckenaer, 1837 is revised, a generic diagnosis is given and an identification key to eight species groups is provided. Olios in its revised sense includes 87 species and is distributed in Africa, southern Europe and Asia. Three species groups are revised in this first part, an identification key to species for each group is provided, five new species are described and all included species are illustrated. The Olios argelasius-group includes O. argelasius Walckenaer, 1806, O. canariensis (Lucas, 1838), O. pictus (Simon, 1885), O. fasciculatus Simon, 1880 and O. kunzi spec. nov. (male, female; Namibia, Zambia, South Africa); it is distributed in the Mediterranean region, northern Africa including Canary Islands, in the Middle East, South Sudan, East Africa, and southern Africa. The Olios coenobitus-group includes O. angolensis spec. nov. (male; Angola), O. coenobitus Fage, 1926, O. denticulus spec. nov. (male; Java), O. erraticus Fage, 1926, O. gambiensis spec. nov. (male, female; Gambia), O. milleti (Pocock, 1901b), O. mordax (O. Pickard-Cambridge, 1899) and O. pusillus Simon, 1880; it is distributed in Africa (Gambia, Angola, Tanzania, Madagascar) and Asia (India, Sri Lanka, Indonesia: Java). The Olios auricomis-group includes only O. auricomis (Simon, 1880), distributed in Africa south of 10°N. Other species groups are introduced briefly and will be revised in forthcoming revisions. The Olios correvoni-group includes currently O. claviger (Pocock, 1901a), O. correvoni Lessert, 1921, O. correvoni choupangensis Lessert, 1936, O. darlingi (Pocock, 1901a), O. faesi Lessert, 1933, O. freyi Lessert, 1929, O. kassenjicola Strand, 1916b, O. kruegeri (Simon, 1897a), O. quadrispilotus (Simon, 1880) comb. nov., O. lucieni comb. nov. nom. nov., O. sjostedti Lessert, 1921 and O. triarmatus Lessert, 1936; it is distributed in Africa (Zimbabwe, Tanzania incl. Zanzibar, Angola, Congo, Central Africa, South Africa, Botswana; O. darlingi was recorded from Zimbabwe and Botswana and not from South Africa). The Olios rossettii-group includes: O. baulnyi (Simon, 1874), O. bhattacharjeei (Saha & Raychaudhuri, 2007), O. brachycephalus Lawrence, 1938, O. floweri Lessert, 1921, O. jaldaparaensis Saha & Raychaudhuri, 2007, O. japonicus Jäger & Ono, 2000, O. kolosvaryi (Caporiacco, 1947b) comb. nov., O. longipes (Simon, 1884b), O. lutescens (Thorell, 1894), O. mahabangkawitus Barrion & Litsinger, 1995, O. obesulus (Pocock, 1901b), O. rossettii (Leardi, 1901), O. rotundiceps (Pocock, 1901b), O. sericeus (Kroneberg, 1875), O. sherwoodi Lessert, 1929, O. suavis (O. Pickard-Cambridge, 1876), O. tarandus (Simon, 1897d), O. tener (Thorell, 1891) and O. tiantongensis (Zhang & Kim, 1996); it is distributed in the Mediterranean region, in Africa (especially eastern half) and Asia (Middle East and Central Asia to Japan, Philippines and Java). The Olios nentwigi-group includes O. diao Jäger, 2012, O. digitatus Sun, Li & Zhang, 2011, O. jaenicke Jäger, 2012, O. muang Jäger, 2012, O. nanningensis (Hu & Ru, 1988), O. nentwigi spec. nov. (male, female; Indonesia: Krakatau), O. perezi Barrion & Litsinger, 1995, O. scalptor Jäger & Ono, 2001 and O. suung Jäger, 2012; it is distributed in Asia (Thailand, Laos, Vietnam, Cambodia, China, Taiwan, Indonesia, Philippines), Papua New Guinea and Mariana Islands. Olios diao is newly recorded from Cambodia and Champasak Province in Laos. The Olios stimulator-group includes O. admiratus (Pocock, 1901b), O. hampsoni (Pocock, 1901b), O. lamarcki (Latreille, 1806) and O. stimulator Simon, 1897c; it is distributed in Africa (Madagascar, Seychelles), Middle East and South Asia (United Arab Emirates, Iraq, Afghanistan, Pakistan, India, Maldives, Sri Lanka). The Olios hirtus-group includes O. bungarensis Strand, 1913b, O. debalae (Biswas & Roy, 2005), O. ferox (Thorell, 1892), O. hirtus (Karsch, 1879a), O. igraya (Barrion & Litsinger, 1995) comb. nov., O. menghaiensis (Wang & Zhang, 1990), O. nigrifrons (Simon, 1897b), O. punctipes Simon, 1884a, O. punctipes sordidatus (Thorell, 1895), O. pyrozonis (Pocock, 1901b), O. sungaya (Barrion & Litsinger, 1995) comb. nov., O. taprobanicus Strand, 1913b and O. tikaderi Kundu et al., 1999; it is distributed in South, East and Southeast Asia (Sri Lanka, India, Nepal, Bangladesh, Myanmar, China, Laos, Thailand, Cambodia, Vietnam, Malaysia, Indonesia, Philippines). Nineteen synonyms are recognised: Nisueta Simon, 1880, Nonianus Simon, 1885, both = Olios syn. nov.; O. spenceri Pocock, 1896, O. werneri (Simon, 1906a), O. albertius Strand, 1913a, O. banananus Strand, 1916a, O. aristophanei Lessert, 1936, all = O. fasciculatus; O. subpusillus Strand, 1907c = O. pusillus; O. schonlandi (Pocock, 1900b), O. rufilatus Pocock, 1900c, O. chiracanthiformis Strand, 1906, O. ituricus Strand, 1913a, O. isongonis Strand, 1915, O. flavescens Caporiacco, 1941 comb. nov., O. pacifer Lessert, 1921, all = O. auricomis; Olios sanguinifrons (Simon, 1906b) = O. rossettii Leardi, 1901; O. phipsoni (Pocock, 1899), Sparassus iranii (Pocock, 1901b), both = O. stimulator; O. fuligineus (Pocock, 1901b) = O. hampsoni. Nine species are transferred to Olios: O. gaujoni (Simon, 1897b) comb. nov., O. pictus comb. nov., O. unilateralis (Strand, 1908b) comb. nov. (all three from Nonianus), O. affinis (Strand, 1906) comb. nov., O. flavescens Caporiacco, 1941 comb. nov., O. quadrispilotus comb. nov., O. similis (Berland, 1922) comb. nov. (all four from Nisueta), O. sungaya (Barrion & Litsinger, 1995) comb. nov., O. igraya (Barrion & Litsinger, 1995) comb. nov. (both from Isopeda L. Koch 1875). Olios lucieni nom. nov. comb. nov. is proposed for Nisueta similis Berland, 1922, which becomes a secondary homonym. The male of O. quadrispilotus comb. nov. is described for the first time. Sixteen species are currently without affiliation to one of the eight species groups: O. acolastus (Thorell, 1890), O. alluaudi Simon, 1887a, O. batesi (Pocock, 1900c), O. bhavnagarensis Sethi & Tikader, 1988, O. croseiceps (Pocock, 1898b), O. durlaviae Biswas & Raychaudhuri, 2005, O. gentilis (Karsch, 1879b), O. gravelyi Sethi & Tikader, 1988, O. greeni (Pocock, 1901b), O. inaequipes (Simon 1890), O. punjabensis Dyal, 1935, O. ruwenzoricus Strand, 1913a, O. senilis Simon, 1880, O. somalicus Caporiacco, 1940, O. wroughtoni (Simon, 1897c) and O. zulu Simon, 1880. Five of these species are illustrated in order to allow identification of the opposite (male) sex and to settle their systematic placement. Thirty-seven species are considered nomina dubia, mostly because they were described from immatures, three of them are illustrated: O. abnormis (Blackwall, 1866), O. affinis (Strand, 1906) comb. nov., O. africanus (Karsch, 1878), O. amanensis Strand, 1907a, O. annandalei (Simon, 1901), O. bivittatus Roewer, 1951, O. ceylonicus (Leardi, 1902), O. conspersipes (Thorell, 1899), Palystes derasus (C.L. Koch, 1845) comb. nov., O. detritus (C.L. Koch, 1845), O. digitalis Eydoux & Souleyet, 1842, O. exterritorialis Strand, 1907b, O. flavovittatus (Caporiacco, 1935), O. fugax (O. Pickard-Cambridge, 1885), O. guineibius Strand, 1911c, O. guttipes (Simon, 1897a), O. kiranae Sethi & Tikader, 1988, O. longespinus Caporiacco, 1947b, O. maculinotatus Strand, 1909, O. morbillosus (MacLeay, 1827), O. occidentalis (Karsch, 1879b), O. ornatus (Thorell, 1877), O. pagurus Walckenaer, 1837, O. patagiatus (Simon, 1897b), O. praecinctus (L. Koch, 1865), O. provocator Walckenaer, 1837, O. quesitio Moradmand, 2013, O. quinquelineatus Taczanowski, 1872, O. sexpunctatus Caporiacco, 1947a, Heteropoda similaris (Rainbow, 1898) comb. rev., O. socotranus (Pocock, 1903), O. striatus (Blackwall, 1867), O. timidus (O. Pickard-Cambridge, 1885), Remmius variatus (Thorell, 1899) comb. nov., O. vittifemur Strand, 1916b, O. wolfi Strand, 1911a and O. zebra (Thorell, 1881). Eighty-nine species are misplaced in Olios but cannot be affiliated to any of the known genera. They belong to the subfamilies Deleninae Hogg, 1903, Sparassinae Bertkau, 1872 and Palystinae Simon, 1897a, nineteen of them are illustrated: O. acostae Schenkel, 1953, O. actaeon (Pocock, 1898c), O. artemis Hogg, 1915, O. atomarius Simon, 1880, O. attractus Petrunkevitch, 1911, O. auranticus Mello-Leitão, 1918, O. benitensis (Pocock, 1900c), O. berlandi Roewer, 1951, O. biarmatus Lessert, 1925, O. canalae Berland, 1924, O. caprinus Mello-Leitão, 1918, O. chelifer Lawrence, 1937, O. chubbi Lessert, 1923, O. clarus (Keyserling, 1880), O. coccineiventris (Simon, 1880), O. corallinus Schmidt, 1971, O. crassus Banks, 1909, O. debilipes Mello-Leitão, 1945, O. discolorichelis Caporiacco, 1947a, O. erroneus O. Pickard-Cambridge, 1890, O. extensus Berland, 1924, O. fasciiventris Simon, 1880 , O. feldmanni Strand, 1915, O. fimbriatus Chrysanthus, 1965, O. flavens Nicolet, 1849, O. fonticola (Pocock, 1902), O. formosus Banks, 1929, O. francoisi (Simon, 1898a), O. fulvithorax Berland, 1924, O. galapagoensis Banks, 1902, O. gaujoni (Simon, 1897b) comb. nov., O. giganteus Keyserling, 1884, O. hoplites Caporiacco, 1941, O. humboldtianus Berland, 1924, O. insignifer Chrysanthus, 1965, O. insulanus (Thorell, 1881), O. keyserlingi (Simon, 1880), O. lacticolor Lawrence, 1952, O. lepidus Vellard, 1924, O. longipedatus Roewer, 1951, O. machadoi Lawrence, 1952, O. macroepigynus Soares, 1944, O. maculatus Blackwall, 1862, O. marshalli (Pocock, 1898a), O. mathani (Simon, 1880), O. minensis Mello-Leitão, 1917, O. monticola Berland, 1924, O. mutabilis Mello-Leitão, 1917, O. mygalinus Doleschall, 1857, O. mygalinus cinctipes Merian, 1911, O. mygalinus nirgripalpis Merian, 1911, O. neocaledonicus Berland, 1924, O. nigristernis (Simon, 1880), O. nigriventris Taczanowski, 1872, O. oberzelleri Kritscher, 1966, O. obscurus (Keyserling, 1880), O. obtusus F.O. Pickard-Cambridge, 1900, O. orchiticus Mello-Leitão, 1930, O. oubatchensis Berland, 1924, O. paraensis (Keyserling, 1880), O. pellucidus (Keyserling, 1880), O. peruvianus Roewer, 1951, O. pictitarsis Simon, 1880, O. plumipes Mello-Leitão, 1937, O. princeps Hogg, 1914, O. pulchripes (Thorell, 1899), O. puniceus (Simon, 1880), O. roeweri Caporiacco, 1955a, O. rubripes Taczanowski, 1872, O. rubriventris (Thorell, 1881), O. rufus Keyserling, 1880, O. sanctivincenti (Simon, 1898b), O. similis (O. Pickard-Cambridge, 1890), O. simoni (O. Pickard-Cambridge, 1890), O. skwarrae Roewer, 1933, O. spinipalpis (Pocock, 1901a), O. stictopus (Pocock, 1898a), O. strandi Kolosváry, 1934, O. subadultus Mello-Leitão, 1930, O. sulphuratus (Thorell, 1899), O. sylvaticus (Blackwall, 1862), O. tamerlani Roewer, 1951, O. tigrinus (Keyserling, 1880), O. trifurcatus (Pocock, 1900c), O. trinitatis Strand, 1916a, O. velox (Simon, 1880), O. ventrosus Nicolet, 1849, O. vitiosus Vellard, 1924 and O. yucatanus Chamberlin, 1925. Seventeen taxa are transferred from Olios to other genera within Sparassidae, eight of them are illustrated: Adcatomus luteus (Keyserling, 1880) comb. nov., Eusparassus flavidus (O. Pickard-Cambridge, 1885) comb. nov., Palystes derasus (C.L. Koch, 1845) comb. nov., Heteropoda similaris (Rainbow, 1898) comb. rev., Remmius variatus (Thorell, 1899) comb. nov., Nolavia audax (Banks, 1909) comb. nov., Nolavia antiguensis (Keyserling, 1880) comb. nov., Nolavia antiguensis columbiensis (Schmidt, 1971) comb. nov., Nolavia fuhrmanni (Strand, 1914) comb. nov., Nolavia helva (Keyserling, 1880) comb. nov., Nolavia stylifer (F.O. Pickard-Cambridge, 1900) comb. nov., Nolavia valenciae (Strand, 1916a) comb. nov., Nungara cayana (Taczanowski, 1872) comb. nov., Polybetes bombilius (F.O. Pickard-Cambridge, 1899) comb. nov., Polybetes fasciatus (Keyserling, 1880) comb. nov., Polybetes hyeroglyphicus (Mello-Leitão, 1918) comb. nov. and Prychia paalonga (Barrion & Litsinger, 1995) comb. nov. One species is transferred from Olios to the family Clubionidae Wagner, 1887: Clubiona paenuliformis (Strand, 1916a) comb. nov.